Self-Empowerment Strategies Reflected by the Main Character in Gebeyehu Ayele’s Escape (2011) - Belete, Kidist; Yazbec, Olga (Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
African women developed indigenous feminist theories because they believed that Western Feminism could not answer the needs of African women. The reasons are cultural differences and differences in African women’s experiences compared to those of Western women. This study analyzes female self-empowerment in the young adult novel Escape (2011) by Gebeyehu Ayele. The novel is written for Ethiopian young adults, but it also appeals to adults. An analysis of the young adult female protagonist is conducted using parameters drawn from snail-sense feminist theory. The article uses textual analysis. The researchers apply the strategies of Snail Sense Feminism, i.e., good education, dialogue with patriarchy, and self-actualization, among others, to extract selected passages from the novel to explore how the female protagonist empowers herself and navigates patriarchy with patience and resilience, paving the way for her freedom from the grip of patriarchal oppression. The female character experiences patriarchal oppression within her household. Through resilience, self-determination, patience, tact, her ability to navigate patriarchy, and support from sisterhood, she succeeds in liberating herself from the yoke of patriarchy.